Toward Country-led Development : A Multi-Partner Evaluation of the Comprehensive Development Framework--Synthesis Report - World Bank (Washington, DC, 2013)
This evaluation report synthesizes the findings of a multi-partner effort to assess implementation of the Comprehensive Development Framework (CDF). The evaluation's primary objectives are to: Identify the factors that have facilitated implementation of CDF principles, and those that have hindered it. Assess the extent to which CDF implementation has affected intermediate outcomes and, to the extent possible, longer-term development outcomes. In the mid-1990s, the aid community began a candid self-assessment. Disappointing development results-especially in Sub-Saharan Africa-had raised troubling questions: Does the emphasis on structural adjustment ignore the poor? Do the many agencies and international organizations working in developing countries overburden, rather than strengthen, the capacity of recipient governments? Does the poor coordination of donors add to the challenge of making development effective? Increasingly, the painful realization of development agencies, recipient countries, and aid analysts was "yes"-the full potential of international aid to reduce poverty by achieving positive, sustainable development results was not being fulfilled.